Investment Knowledge, Risk Perception, and Income as Determinants of Students’ Investment Interest: Evidence from an Indonesian Islamic University - Ratna Nurani; Fitra Al Hadro (Yayasan Pendidikan Islam Al-Matani, 2025)
This study examines the effects of investment knowledge, risk perception, and income on students’ investment interest at the Faculty of Economics and Social Sciences, Universitas Islam Negeri Sultan Syarif Kasim Riau, Indonesia. A quantitative research design was employed, with primary data collected through questionnaires administered to 99 students selected using proportionate stratified random sampling. The data were analyzed using multiple linear regression with SPSS. The findings reveal that investment knowledge and income have positive and statistically significant effects on investment interest, whereas risk perception does not exhibit a significant influence. The coefficient of determination (R²) of 0.838 indicates that the proposed variables explain 83.8% of the variance in students’ investment interest, while the remaining 16.2% is attributable to other factors not included in this model. These results underscore the importance of strengthening financial literacy and improving students’ income capacity to enhance investment participation. Meanwhile, risk perception appears to be less influential, possibly due to students’ greater emphasis on expected returns. This study contributes to the empirical literature on investment behavior among university students and provides practical implications for higher education institutions and policymakers in promoting investment awareness and financial education.